2012
DOI: 10.1021/jf301109p
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Acid Hydroxamate Downregulated the Melanin Synthesis and Tyrosinase Activity through Activating the MEK/ERK and AKT/GSK3β Signaling Pathways

Abstract: In this study, nicotinic acid hydroxamate (NAH), a nicotinic acid derivative, was found to show dose-dependent inhibition of melanin content and tyrosinase activity of murine melanoma B16F10 cells with or without being cotreated with cAMP stimulators. In the studies on signaling pathways for skin whitening, NAH-treated B16F10 cells resulted in a decrease in the expression of tyrosinase, tyrosinase-related protein-1, and microphthalmia-associated transcription factor (MITF). PD98059 and LY294002 additions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 31 publications
(56 reference statements)
1
21
0
1
Order By: Relevance
“…The B16F10 melanoma cells were cultured following the methods of Lin et al (2012b). Different concentrations of GH, Gly and arbutin (0.5-3.5 mM) were added to a seeded 24-well microtiter plate and incubated in a humidified incubator at 5 % CO 2 and 37 °C for 24 h. Five microliter of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT, 5 mg/mL) was added under light protection and after 4 h, 100 μL of DMSO was added to dissolve the formed formazans.…”
Section: Cell Culture and Cell Viability Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…The B16F10 melanoma cells were cultured following the methods of Lin et al (2012b). Different concentrations of GH, Gly and arbutin (0.5-3.5 mM) were added to a seeded 24-well microtiter plate and incubated in a humidified incubator at 5 % CO 2 and 37 °C for 24 h. Five microliter of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT, 5 mg/mL) was added under light protection and after 4 h, 100 μL of DMSO was added to dissolve the formed formazans.…”
Section: Cell Culture and Cell Viability Assaymentioning
confidence: 99%
“…The absorbance values at 475 nm were compared against a standard curve of mushroom TYR. To determine melanin content in B16F10 cells, the extraction and analysis were performed as per the previous report (Lin et al 2012b). …”
Section: Determination Of Cellular Tyr Activity and Melanin Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammalian melanocytes, melanogenesis is controlled at least by three regulatory proteins, tyrosinase, and TRP1 and TRP2. In contrast, hyperpigmentation is by overactivity of TRPs, but not all skin-whitening agents can simultaneously inhibit TYR, TRP-1, and TRP-2, such as Arthrophytum scoparium, Glechoma hederacea and nicotinic acid hydroxamat [18][19][20] . However, our Western blotting assay showed that CCE treatment reduced the expression of all rate-limiting enzymes, including tyrosinase, TRP-1, and TRP-2 protein, and prevented abnormal accumulation of melanin in the process of melanogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of tyrosinase, TRP-1, TRP-2, and MITF in B16F10 cells by Western blot was undertaken as described previously by Yoon 20. Tyrosinase, TRP-1, TRP-2 and MITF bands were detected with the rabbit polyclonal anti-tyrosinase antibody (dilution 1:1 000), anti-TRP-1 antibody (dilution 1:1 000), anti-TRP-2 antibody and anti-MITF antibody (dilution 1:500), respectively, which were purchased from Santa Cruz Biotechnology (Santa Cruz, CA, USA), and then further incubated with horseradish peroxidase-conjugated antirabbit IgG antibody at a 1:5 000 dilution.…”
Section: Analysis Of the Expression Of Proteins Regulating Melanogenementioning
confidence: 99%